PsRPs26, a 40S Ribosomal Protein Subunit, Regulates the Growth and Pathogenicity of Puccinia striiformis f. sp. Tritici - Wang, Bing; Song, Na; Tang, Chunlei; Ma, Jinbiao; Wang, Ning; Sun, Yanfei; Kang, Zhensheng (Frontiers in Microbiology, 2019)
The eukaryotic ribosome is the cellular translational machinery that is primarily responsible for protein synthesis, which is essential for cell growth, proliferation, differentiation, and animal development. RPs26 is an essential structural protein of the ribosomal subunit. However, little is known about the function of RPs26 in pathogenic fungi. In this study, we isolated an RPs26 gene from wheat inoculated with the stripe rust pathogen Puccinia striiformis f. sp. tritici (Pst), designated PsRPs26. PsRPs26 contains a typical conserved Y62–K70 motif and shares more than 90% identity with its orthologs from other fungi. PsRPs26 localized to both the nucleus and cytoplasm. Expression of PsRPs26 obviously increased when host plants were infected with the Pst CYR31 isolate. Moreover, knockdown of PsRPs26 by a host-induced gene silencing system inhibited the growth and virulence of Pst. These results provide new insight into the function of PsRPs26 in cereal rust fungi and might be useful in the search for, and design of, novel disease control strategies.